The sunshine problem: Climate change and managed decline in the European Union - Timur Ergen; Luuk Schmitz (Max Planck Institute for the Study of Societies, 2023)
Decarbonization requires the winding down of - economically - fully viable, if not highly prosperous, lines of economic activity. Different from past episodes of industrial restructuring revolving around the managed decline of sunset industries, accelerating climate change requires reallocation away from economic activities where the metaphorical sun is still shining. Firms, owners, workers, regions, and polities structurally rely on these sources of prosperity and have interwoven their past and future lives with them. We argue that this problem has created a space for state actors to experiment with vertical industrial policies to manage the reallocation of resources from polluting to non-polluting activities. We illustrate this dynamic by investigating the least-likely case of the European Union, a polity heavily tilted towards market governance. European climate policymakers, we argue, have incrementally moved away from the primacy of regulatory, market-making tools and have introduced a plethora of vertical instruments to shift resources away from climate-harming fields. This experimentation with vertical policies unfolds against the backdrop of a thirty-year institutional legacy of single market-oriented policy in the energy field. – – Dekarbonisierung erfordert die Abwicklung und Restrukturierung von - wirtschaftlich - überlebensfähigen, wenn nicht sogar prosperierenden Wirtschaftszweigen. Anders als in früheren industriellen Restrukturierungsprozessen, bei denen es um die kontrollierte Herunterskalierung von 'Sunset-' oder 'Problemindustrien' ging, macht die Beschleunigung des Klimawandels eine Umverteilung weg von wirtschaftlichen Aktivitäten erforderlich, über denen die metaphorische Sonne noch scheint. Unternehmen, Kapitaleignerinnen und Kapitaleigner, Arbeitnehmerinnen und Arbeitnehmer, Regionen und Staaten bleiben strukturell auf diese Aktivitäten angewiesen und haben ihr Leben mit ihnen verwoben. Wir argumentieren, dass dieses Problem einen Raum für staatliche Akteure geschaffen hat, mit vertikalen industriepolitischen Maßnahmen zu experimentieren, um die Umverteilung von Ressourcen von umweltverschmutzenden zu nicht umweltverschmutzenden Aktivitäten zu befördern. Wir veranschaulichen diese Dynamik anhand einer Fallstudie der Europäischen Union, ein institutionelles Gefüge, das traditionell stark auf marktwirtschaftliche Steuerung ausgerichtet ist. Wir argumentieren, dass sich die europäische Klimapolitik schrittweise vom Primat der regulatorischen, marktwirtschaftlichen Instrumente entfernt und eine Fülle von vertikalen Instrumenten eingeführt hat, um den Ressourcenentzug aus klimaschädlichen Bereichen zu ermöglichen. Dieses Experimentieren mit vertikalen Politikinstrumenten vollzieht sich vor dem Hintergrund eines 30-jährigen institutionellen Erbes marktorientierter Politik im Energiesektor.
hdl:21.11116/0000-000E-27B9-6
Keywords: 300; climate change; cohesion policy; European Union; green transition; industrialpolicy; regional restructuring; Energiewende; Europäische Union; Industriepolitik; Klimawandel; Kohäsionspolitik; regionaler Strukturwandel